2021
DOI: 10.3389/fpsyt.2021.665402
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Theta-Burst Stimulation Transcranial Magnetic Stimulation Increases GABA in the Medial Prefrontal Cortex: A Preliminary Sham-Controlled Magnetic Resonance Spectroscopy Study in Acute Bipolar Depression

Abstract: Background: Magnetic resonance spectroscopy (MRS) has been used to identify gamma-aminobutyric acid (GABA) alterations in mood disorders, particularly in the medial prefrontal cortex (mPFC) where decreased concentrations have been associated with anhedonia. In major depressive disorder (MDD), prior work suggests that repetitive transcranial magnetic stimulation (rTMS) increases mPFC GABA concentrations proportional to antidepressant response. To our knowledge, this has not been examined in acute bipolar depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Based on the analysis of both normal and tangential components of the EFs in modulating prefrontal cortex, Csifcsak et al reported that strong stimulation can be found not only in DLPFC but also in the medial prefrontal cortex (MPFC) in bipolar montages which are commonly used for depression [21]. Their study supported previous modeling studies that have suggested the medial prefrontal cortex as a new target for depression in TMS studies [22,23]. In another example of atlas-based parcellation of the computational head models, four different electrode arrangements were simulated for a single standard subject (ICBME152) and 22 cortical areas were extracted per hemisphere [22].…”
Section: Introductionmentioning
confidence: 66%
“…Based on the analysis of both normal and tangential components of the EFs in modulating prefrontal cortex, Csifcsak et al reported that strong stimulation can be found not only in DLPFC but also in the medial prefrontal cortex (MPFC) in bipolar montages which are commonly used for depression [21]. Their study supported previous modeling studies that have suggested the medial prefrontal cortex as a new target for depression in TMS studies [22,23]. In another example of atlas-based parcellation of the computational head models, four different electrode arrangements were simulated for a single standard subject (ICBME152) and 22 cortical areas were extracted per hemisphere [22].…”
Section: Introductionmentioning
confidence: 66%
“…As of now, multiple studies allowed the formulation of several theories attempting to elucidate the pathogenesis of depression, including the monoamine [ 50 ], cytokine [ 51 ], HPA hyperactivity [ 52 ], neuroinflammation and neuroplasticity [ 53 ], GABA-glutamate-mediated depression [ 54 ], and circadian hypotheses [ 55 ]. These theoretical studies show that depression is a complex mental disorder involving a variety of neurotransmitters, brain regions, circuits and various biochemical substances or/and systems.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both GABAergic synapse and neurotrophic signaling pathways (BDNF-Ntrk2) were involved in the antidepressant and anti-anxiety effects of the LBRD standard decoction in both in vitro and in vivo models. Reduction in BDNF and GABA neurotransmission co-occur in the mPFC tissues and has been repeatedly seen in animal models and human subjects, and this has been associated with anhedonia and anxiety [ 54 , 79 – 82 ]. In addition, treatment with antidepressants and anti-anxiety agents, as well as repetitive transcranial magnetic stimulation treatment has been shown to enhance GABA and BDNF expression in depression [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors attempted to determine the efficacy of iTBS to treat acute BD using an antimanic drug combined with iTBS in the left dlPFC but found that this method was ineffective [9]. Interestingly, another study pointed out an increase in mPFC GABA levels after left dlPFC iTBS treatment, but this was not associated with improvement in depression symptoms in BD [10]. Thus, a different mechanism could exist in BD.…”
Section: Non-invasive Approachesmentioning
confidence: 99%